Inhibition of VDAC1 oligomerization blocks cysteine deprivation-induced ferroptosis via mitochondrial ROS suppression - Se-Kyeong Jang; Se Hee Ahn; Gyeongmi Kim; Selim Kim; Jungil Hong; Ki Soo Park; In-Chul Park; Hyeon-Ok Jin (Cell Death and Disease)
Abstract Ferroptosis, a regulated form of cell death dependent on reactive oxygen species (ROS), is characterized by iron accumulation and lethal lipid peroxidation. Mitochondria serve as the primary source of ROS and thus play a crucial role in ferroptosis initiation and execution. This study highlights the role of mitochondrial ROS and the significance of voltage-dependent anion channel 1 (VDAC1) oligomerization in ferroptosis induced by cysteine deprivation or ferroptosis-inducer RSL3. Our results demonstrate that the mitochondria-targeted antioxidants MitoQ and MitoT effectively block ferroptosis induction and that dysfunction of complex III of the mitochondrial electron transport chain contributes to ferroptosis induction. Pharmacological inhibitors that target VDAC1 oligomerization have emerged as potent suppressors of ferroptosis that reduce mitochondrial ROS production. These findings underscore the critical involvement of mitochondrial ROS production via complex III of the electron transport chain and the essential role of VDAC1 oligomerization in ferroptosis induced by cysteine deprivation or RSL3. This study deepens our understanding of the intricate molecular networks governing ferroptosis and provides insights into the development of novel therapeutic strategies targeting dysregulated cell death pathways.